Structural framework, evidence of neotectonic activity and drainage reorganization in the eastern piedmont of Famatina-Sañogasta ranges (latitudes 29°15′— 29°35′S), Argentina - Canelo, Horacio N. (2026)
This study investigates the structural architecture and neotectonics of a region in the eastern piedmont of the Famatina and Sañogasta ranges in the Sierras Pampeanas, central-western Argentina. The area has undergone W-E horizontal compression since the Neogene. Despite its geodynamic importance as part of the southern Central Andes under Pampean flat-slab subduction, its structural and neotectonic framework remains poorly understood. Prior research has focused primarily on lithostratigraphy and geomorphology. This study provides a novel structural synthesis to explain Quaternary deformation and ongoing morphotectonic evolution in this setting. Through geologic mapping, remote sensing, GPS surveys, and aeromagnetic data, we identify a system of ∼N/S-striking, basement-involved blind reverse faults. These include east-vergent backthrusts linked to the Sañogasta Range uplift and a major west-vergent fault, collectively forming a thick-skinned triangle zone. Flexural scarps, deformed terraces, sag ponds, and drainage anomalies evidence neotectonic activity. The distribution of the “conglomerados amarillos” unit reveals a major Pleistocene-Holocene reorganization of the drainage of the El Oro River. This unit records an acidic paleodrainage system sourced from the Nevados de Famatina Mining District. The subsequent uplift of the Bordo de Guanchín-Sañogasta hill in the Pleistocene-Holocene era diverted the river from its original path toward the Lomadas de Nonogasta hills, redirecting it to its present course near Chilecito City. This work establishes a structural framework for Quaternary deformation during ongoing flat-slab subduction. However, limitations persist due to the blind nature of faults and a lack of high-resolution geophysical and geochronological data to quantify shortening rates and seismic recurrence.